Knowledge Management Factors and Its Impact on Organizational Performance: A Systematic Literature Review - Slamet Darmawan; Novia Agusvina; Sofian Lusa; Dana Indra Sensuse (JOIV : International Journal on Informatics Visualization, 2023)
Knowledge management can help organizations to improve their performance. Many studies show that knowledge management impacts organizational performance. Human capital is considered a mediating role in knowledge management's impact on organizational performance, but it is still blurred, and only a few studies are related to this issue. Moreover, various factors influence knowledge management, such as organizational structure, culture, technology, strategy, trust, and leadership, but maybe other factors have not been identified. This factor can help knowledge management impacts organizational performance. This study was conducted to determine how the human capital role mediates the impact of knowledge management on organizational performance and determine another factor that affects knowledge management, which can impact organizational performance. This study was based on the Systematic Literature Review (SLR), which includes 37 articles published from 2016 to 2021. The study showed that human capital mediates the impact of knowledge management on organizational performance directly and indirectly through innovation. Meanwhile, organizational structure, culture, trust, leadership, human behavior, human resources practices, technology, and strategy are identified as factors that affect knowledge management, whereas human resources practices affect human behavior and leadership. Finally, we proposed a conceptual model that described how knowledge management factors impact human capital and organizational performance. This research can contribute to enriching knowledge management theory and be used to give recommendations for improving the implementation of knowledge management. Further research involves data collection, and empirical analysis needs to be conducted in an organization to examine the conceptual model.